REVISITING THE MULTIFACTOR LEADERSHIP QUESTIONNAIRE: MEDIATING ROLE OF LEADERSHIP STYLES, ORGANIZATIONAL CULTURE, AND PERFORMANCE. - Ghulam Muhammad Kundi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Purpose: Leadership is one of the important factors, and responsible for the performance of employees. Leaders use culture as a key to enhance the performance of employees. The purpose of this research is to extend previous empirical studies on leadership by testing organizational culture as an underlying mechanism between leadership and performance. Design: A deductive, quantitative, cross-sectional survey was employed. The cross-cultural sampling was done, sample respondents belong to Pakistan, and Malaysia with a sample size of 319 employees to test the hypotheses. PLS-SEM 3 was used for data analysis. Findings: The results reveal that attributes of leadership (transformational & transactional) were positively related to performance. In addition, culture was also positively related to performance. Culture does act as a mediator between transformational leadership style, and performance but there is no mediating effect of culture between transactional leadership style, and performance. Leaders can enhance the performance of their employees by showing flexible behavior and can link rewards on completion of task. Once this culture is set, the performance could be improved. Moreover, leaders must avoid discrimination in sanctioning rewards to employees, and they should be treated equally. This will increase teamwork and team spirit. Originality/ Value: This study highlighted the importance of culture which is an important factor between leadership and performance, and this model was tested in public sector organizations i.e. developing countries.